Keynes and modern economics - Kuroki, Ryuzo, 1953- (Routledge studies in the history of economics ;, 2013)
It is a little over seventy years since John Maynard Keynes produced his magnum opus, The General Theory of Employment, Interest, and Money. Keynes' staggering achievement has been to remain relevant to economics and other disciplines even today and this book reflects that with an examination on his influence on modern economics.Leading economists from a variety of backgrounds, including Ed Nell and Heinz Kurz have joined forces in this volume with internationally respected Japanese scholars to produce a strong collection of contributions to the debate on Keynes' monumental.